GAMBARAN PSIKOLOGIS PEROKOK TEMBAKAU YANG BERALIH MENGGUNAKAN ROKOK ELEKTRIK (VAPORIZER) - Indra, Muhammad Fikri; Hasneli N, Yesi '; Utami, Sri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This research was qualitative study with descriptive phenomenology approach. The purpose was to describe psychological that are cognitive, emotional, and behavioral changes that occur on tobacco smokers who switch to use electric cigarette (vaporizer). Five respondents were selected by purposive sampling method and used theory of saturation. Data were collected by in-depth interviews which completed by field note and analyzed by Colaizzi method. This research identified three themes: perception about vaporizer, emotion when using vaporizer, and behavioral changes. This research recommends that the need to know the psychological changes such as perception and uncontrolled positive emotions that occur on vaporizer user, so nurse can give promotive and preventive proceeding agains device and hazardous liquid. Keywords: electric cigarette, psychological, vaporizer References: 63 (1982-2014)